1992
DOI: 10.1111/j.1476-5381.1992.tb14511.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic antihypertensive treatment with captopril plus hydrochlorothiazide improves aortic distensibility in the spontaneously hypertensive rat

Abstract: Adult male spontaneously hypertensive rats (SHR) were given captopril plus hydrochlorothiazide mixed in the diet for 10 weeks. Calculated daily doses were 44 mg kg−1 per day for captopril, and 22 mg kg−1 per day for hydrochlorothiazide. Separate groups received captopril or hydrochlorothiazide alone, at similar doses, or no treatment. A final group of WKY normotensive rats received no drug. Systolic arterial blood pressure, measured at regular intervals throughout the 10 weeks' period was lowered but not norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“…In this regard, several authors have reported that the reversal of hypertension by chronic ACEi and angiotensin II receptor blockade [9,[11][12][13] could lower systolic arterial BP and aortic stiffness as measured by pulse wave velocity (PWV). The reduction in aortic PWV was associated with structural changes in the vessel wall in both SHR [7] and rat renovascular models of hypertension [14], both associated with a reduction in BP.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several authors have reported that the reversal of hypertension by chronic ACEi and angiotensin II receptor blockade [9,[11][12][13] could lower systolic arterial BP and aortic stiffness as measured by pulse wave velocity (PWV). The reduction in aortic PWV was associated with structural changes in the vessel wall in both SHR [7] and rat renovascular models of hypertension [14], both associated with a reduction in BP.…”
Section: Introductionmentioning
confidence: 99%
“…26 The explanation for this may lie in the relative lack of sensibility of rat microvasculature to ACE inhibitors (unless associated with salidiuretic treatment). 27 It has previously been reported that degradation products of angiotensin such as the hexapeptide Ang II-(3-8) 18 rather than Ang II itself produce arteriolar vasomotor effects. Our experiments neither confirm nor refute this possibility.…”
Section: Vincent Et Al Ang II and Cerebral Arteriole Vasomotion 2693mentioning
confidence: 99%
“…Measurement of pressure pulse wave velocity (PWV) provides values for elastic modulus via the Moens-Korteweg equation. This was first developed to measure aortic elasticity in large mammal species (humans [5]and dogs [6]), then adapted to smaller species such as the rat [7, 8]. More recently, ultrasound technology (using a wall echo-tracking device) has been developed to follow the changes in diameter following a change in pulse pressure.…”
Section: Introductionmentioning
confidence: 99%